The Use of the Quran Belajar Indonesia Application in Quran Learning at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Hidayatut Tholabah, Tegalreja Village, Banjarharjo District, Brebes Regency (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2025)
This study aims to explore the effectiveness of using the Quran Belajar Indonesia application in teaching Qur’anic reading to 4th-grade students at MDTA Hidayatut Tholabah, located in Tegalreja Village, Banjarharjo District, Brebes Regency. The background of the research is based on the need for more engaging, interactive, and digitally aligned learning methods in Qur’anic education, tailored to the characteristics of the digital-native generation. The main issue addressed is the students’ low proficiency in reading the Qur’an, particularly in the areas of tajwid and makharijul huruf, as well as the limitations of conventional teaching methods that have been traditionally applied. This research adopts a descriptive qualitative approach, employing observation, interviews, and documentation as data collection techniques. The research subjects consist of the Qur’an teacher, 4th-grade students, the head of the madrasah, and several students’ parents. Data analysis was conducted through systematic processes of data reduction, presentation, and conclusion drawing. The findings reveal that the integration of the Quran Belajar Indonesia application contributes positively to the learning of Qur’anic reading. The application facilitates students in recognizing Arabic letters interactively, practicing tajwid through color-coded features, and engaging in independent practice. The teacher plays an active role in guiding the use of the application to ensure alignment with learning objectives. Most students demonstrated improved reading skills after using the application, although some still required assistance. Supporting factors for the implementation include the readiness of the teacher, the availability of devices, and the enthusiasm of students. However, challenges remain, such as limited digital infrastructure and low technological literacy. The conclusion of this study indicates that the use of Quran Belajar Indonesia can serve as an innovative and effective alternative in Qur’anic reading instruction at the elementary education level. The study recommends collaboration among teachers, parents, and educational institutions to optimize the integration of technology in religious learning.